Smart Health Care Kit based on IoT - VM, Praveen Kumar; SA, Rajshekhar (International Journal of Computer Sciences and Engineering, 2025)
the past few years have witnessed an increase in the development of wearable sensors for health monitoring systems. This increase has been due to several factors such as development in sensor technology as well as directed efforts on political and stakeholder levels to promote projects, which address the need for providing new methods for care given increasing challenges with an aging population. An important aspect of study in such system is how the data is treated and processed.This project provides a recent review of the latest methods and algorithms used to analyze data from wearable sensors used for physiological monitoring of vital signs in healthcare services. In particular, the project outlines the more common data mining tasks that have been applied such as anomaly detection, prediction and decision-making when considering in particular continuous time series measurements.